The role of a virtual telephone clinic in the follow-up management of lateral skull base tumours. Issue 12 (17th December 2020) - Hogan, S; Hintze, J; Fitzgerald, C; Javadpour, M; Rawluk, D; McConn Walsh, R
Abstract: Objective: The purpose of this article was to determine the impact of employing a telephone clinic for follow-up of patients with stable lateral skull-base tumours. Method: An analysis of 1515 patients in the national lateral skull-base service was performed, and 148 patients enrolled in the telephone clinic to date were identified. The length of time that patients waited for results of their follow-up scans and the travel distance saved by patients not having to attend the hospital for their results was determined. Results: The mean time from scan to receiving results was 30.5 ± 32 days, 14 days sooner than in the face-to-face group ( p = 0.0016). The average round-trip distance travelled by patients to the hospital for results of their scans was 256 ± 131 km. Conclusion: The telephone clinic led to a significant reduction in time until patients received their scan results and helped reduce travel distance and clinic numbers in traditional face-to-face clinics.